How to Keep Oxidative Stress Under Control? - Laetitia Pire; Ginette Deby-Dupont; Thierry Lemineur; Jean-Charles Preiser (Current Nutrition & Food Science, 2007)
An excessive production of oxidants disturbs the normal intracellular equilibrium, and can lead to an “oxidative stress”. Recent data indicate that several components of the regular diet as well as chemical compounds and drugs can modulate the so-called “oxidative stress” both via anti-oxidant effects and via inhibition or activation of the enzymes involved in reactive nitrogen oxygen species (RNOS). We will describe in this review article the biochemistry of oxygen, the physiological roles and regulation of oxidative stress. The clinical relevance of uncontrolled oxidative stress will be presented as well as the results of therapeutic trials with antioxidants. New promising strategies which modulate the activities of the RNOS generating enzymes, with selected catalytic inhibitors will be discussed.
Keywords: reactive nitrogen oxygen species